NEWTON POLYHEDRA AND ESTIMATION TO EXPONENTIAL SUMS - Kamen Ariffin Mohd Atan; J.H Loxton (Proceedings of ICMSA, 2006)
The classical Newton polygon is a device for computing the fractional power series expansions of algebraic functions. Newton gave a number of examples of this process in his ”Method of Fluxions” which amount to a generalmethod.